Roadmap for Renewable Energy Technologies Diffusion : A comparative study of Socioeconomic, Regulatory, and Technological issues in Finland and Poland - Juszczyk, Oskar (Vaasan yliopisto, 2023)
Energy is a fundamental resource required for the functioning and prosperity of societies across the globe. However, due to e.g. industrialization, digitalization, overpopulation, and growing shares of the global middle and middle-high class, the energy demand levels are expeditiously increasing. Considering climate change and global warming issues, there is a need to significantly limit the utilization of fossil fuels for energy generation purposes. Renewable energy technologies (RETs) can support the global energy transition by providing more clean, sustainable, and environmentally-friendly solutions. The expanding technological innovation advancement generates the capacity of renewables to enhance, inter alia, energy efficiency and security, sustainable development, proficient use of native resources, independence from energy imports, and escalating cost competitiveness. Regrettably, the share of renewables in global energy mixes remains relatively modest and inadequate. This doctoral dissertation aims to explore the major factors influencing the diffusion of renewable energy technologies. Particular emphasis has been put on key regulatory, socioeconomic, and technological aspects of RETs diffusion in two European Union member states, Finland and Poland. By applying a problem-solving approach, this study initially detects the most hampering factors of RETs diffusion in order to address them and suggest effective improvement measures. The outcomes of this research highlight the importance of regulatory regimes and inter-sectoral collaborative networks to uphold the diffusion of environmentally-friendly solutions and propose circular economy, venture capital, and blockchain technology as possible incubators for RETs diffusion. Qualitative research methodology, strengthened with the philosophical approach of critical realism has helped to thoroughly investigate the phenomenon of RETs diffusion based on selected case studies from the RETs industry. A cross-country comparative analysis reveals novel insights on major similarities and differences in various predicaments for developing RETs in both investigated countries. The collective outcomes of the analyses served to develop a “Roadmap for RETs diffusion”, which suggests practical mechanisms, actions, and measures to facilitate the adoption of renewables in Finland and Poland. This study is a vital information source for the policymakers, practitioners, and other stakeholders and interest groups devoted to the widespread diffusion of RETs.

Energia on yhteiskuntien toiminnan ja hyvinvoinnin kannalta keskeinen perusresurssi kaikkialla maailmassa. Energian kysyntä kasvaa kuitenkin nopeasti johtuen muun muassa teollistumisesta, digitalisaatiosta ja ylikansoituksesta. Ilmaston lämpenemisen hillitsemiseksi fossiilisten polttoaineiden käyttöä energiantuotantotarkoituksiin on merkittävästi rajoitettava. Uusiutuvan energian teknologiat (RET) voivat tukea maailmanlaajuista energiasiirtymää tarjoamalla puhtaampia, kestävämpiä ja ympäristöystävällisempiä ratkaisuja. Uusiin energialähteisiin liittyvät teknologiset innovaatiot parantavat energiatehokkuutta ja turval¬lisuutta, kestävää kehitystä, luonnonvarojen asiantuntevaa käyttöä, riippu¬mattomuutta energian tuonnista sekä kansallista kustannuskilpailukykyä. Uusiutuvien energialähteiden osuus maailman energiantuotannosta on kuitenkin edelleen suhteellisen vaatimaton. Tämän väitöskirjan tavoitteena on selvittää uusiutuvan energian teknologioiden leviämiseen vaikuttavia keskeisiä tekijöitä. Uusiutuvan energian teknologioiden leviämisen keskeisiä tekijöitä sääntelyn sekä sosioekonomisten ja teknologisten näkökohtien kannalta on tarkasteltu erityisesti kahdessa Euroopan unionin jäsenvaltiossa, Suomessa ja Puolassa. Tutkimuksessa on tunnistettu teknologioiden leviämistä vaikeuttavia tekijöitä ja niihin liittyviä parannuksia. Tutkimuksen tulokset korostavat sääntelyjärjestelmien välisten yhteistyöverkostojen merkitystä ympäristöystävällisten ratkaisujen edistämisessä, ja ehdottavat kierto¬taloutta, riskipääomaa ja lohkoketjuteknologiaa mahdollisiksi ratkaisuiksi uusiutuvan energian teknologioiden leviämiselle. Tutkimus noudattaa kriittiseen realismiin pohjautuvaa laadullista tutkimusmetodologiaa. Uusiutuvan energian teknologioiden leviämistä tutkitaan tapaustutkimuksia käyttäen. Maiden välinen vertaileva analyysi tuo esiin havaintoja merkittävistä yhtäläisyyksistä ja eroista erilaisissa uusiutuvan energian teknologioiden kehityksen haasteissa molemmissa tutkituissa maissa. Analyysien tulosten pohjalta työssä on kehitetty tiekartta, joka ehdottaa käytännön mekanismeja, toimia ja toimenpiteitä uusiutuvien energialähteiden käyttöönoton helpotta¬miseksi Suomessa ja Puolassa. Tämä tutkimus toimii tietolähteenä poliittisille päättäjille, toimijoille ja muille sidosryhmille uusiutuvan energian teknologisen kehityksen alueella.
Keywords: innovations; sustainable development; technology; renewable energy sources; energy technology; energy policy; technological development; biogas; fi=Tuotantotalous|en=Industrial Management|